2022
DOI: 10.1186/s12913-022-08499-w
|View full text |Cite
|
Sign up to set email alerts
|

The readiness of public primary health care (PUSKESMAS) for cardiovascular services in Makasar city, Indonesia

Abstract: Backgrounds The increasing burden of cardiovascular disease (CVD) has become a major challenge globally, including in Indonesia. Understanding the readiness of primary health care facilities is necessary to confront the challenge of providing access to quality CVD health care services. Our study aimed to provide information regarding readiness to deliver CVD health services in public primary health care namely Puskesmas. Methods The study questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This should be a major concern for the healthcare systems, as patients with hypertension with poorly controlled blood pressure are at increased risk of developing or worsening pre-existing cardiovascular, cerebrovascular, and renal diseases, which can lead to high utilization of emergency services that are more costly for the healthcare system [45]. Beyond the ground level implementation, stakeholders in Indonesia should pay more attention to many concerns raised even before the pandemic related to the suboptimal chronic disease management implementation across the board due to overlapping of non-communicable disease (NCD) programs, which leads to overburdened primary healthcare workers [46][47][48]. Streamlining programs and reporting procedures are a few solutions to this [41].…”
Section: Discussionmentioning
confidence: 99%
“…This should be a major concern for the healthcare systems, as patients with hypertension with poorly controlled blood pressure are at increased risk of developing or worsening pre-existing cardiovascular, cerebrovascular, and renal diseases, which can lead to high utilization of emergency services that are more costly for the healthcare system [45]. Beyond the ground level implementation, stakeholders in Indonesia should pay more attention to many concerns raised even before the pandemic related to the suboptimal chronic disease management implementation across the board due to overlapping of non-communicable disease (NCD) programs, which leads to overburdened primary healthcare workers [46][47][48]. Streamlining programs and reporting procedures are a few solutions to this [41].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies carried out in several LMICs, including South Asian nations, found low readiness to offer services for noncommunicable diseases like diabetes [10][11][12], hypertension [13][14][15] and chronic respiratory diseases [14,16,17]. There is, however, a dearth of research on CVD readiness and related factors in LMICs [14,[17][18][19][20][21][22]. However, most earlier studies on the availability of CVD care in low-resource settings relied on proxy measures made up of generic inputs like the number of healthcare workers and hospital beds [22], or were restricted to local or regional samples [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, a dearth of research on CVD readiness and related factors in LMICs [14,[17][18][19][20][21][22]. However, most earlier studies on the availability of CVD care in low-resource settings relied on proxy measures made up of generic inputs like the number of healthcare workers and hospital beds [22], or were restricted to local or regional samples [19][20][21]. The results may be skewed because most earlier studies in this area used small sample sizes, unrepresentative samples, or didn't use a consistent measurement tool to gauge readiness.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, early clinical exposure and community-oriented programs in the public health curriculum are undertaken in Puskesmas [1]. Puskesmas is a government-managed public primary health facility that provides individual or community health services in designated locations [2]. Multidisciplinary teamwork and comprehensive programs Puskesmas in individual and community, including health promotion, surveillance of communicable diseases, family planning, and environmental hygiene, are appropriate for medical students in public health clinical rotations involved in those programs [3].…”
Section: Introductionmentioning
confidence: 99%